2017
DOI: 10.1016/j.tecto.2017.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Seismic scattering and absorption mapping from intermediate-depth earthquakes reveals complex tectonic interactions acting in the Vrancea region and surroundings (Romania)

Abstract: The Vrancea region, located at the southeastern edge of the Carpathians arc bend, is a region of intense seismicity, whose major earthquakes produce hazard in southeastern Europe. Despite the consequent focus of the geophysical and geological community on providing accurate structural and dynamical models of Vrancea, these are still subject to numerous controversies and debates. In the present study, we use intermediate-depth seismicity recorded by the broadband stations of the Romanian Seismic Network between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 71 publications
1
11
0
Order By: Relevance
“…Beneath the East Carpathians, upwelling of low-Vp asthenosphere has been proposed and supported with independent seismic measurements (e.g. Ren et al, 2012;Borleanu et al, 2017). The upwelling hypothesis (Gögüş et al, 2016;Maţenco, 2017;Şengül Uluocak et al, 2019) is also supported by the occurrence of post-collisional volcanism (Seghedi et al, 2011), and the observed high heat flux values (up to mW/m 2 locally, Demetrescu and Veliciu, 1991).…”
Section: Asthenospheric Upwelling In the Transylvanian Intra-arc Basinmentioning
confidence: 58%
“…Beneath the East Carpathians, upwelling of low-Vp asthenosphere has been proposed and supported with independent seismic measurements (e.g. Ren et al, 2012;Borleanu et al, 2017). The upwelling hypothesis (Gögüş et al, 2016;Maţenco, 2017;Şengül Uluocak et al, 2019) is also supported by the occurrence of post-collisional volcanism (Seghedi et al, 2011), and the observed high heat flux values (up to mW/m 2 locally, Demetrescu and Veliciu, 1991).…”
Section: Asthenospheric Upwelling In the Transylvanian Intra-arc Basinmentioning
confidence: 58%
“…We note that seismic attenuation, i.e., 1/Q, would also contribute to frequency-dependent reduction of the ground motion, but the effect is secondary. Sedimentary basins generally have a relatively high attenuation, or low Q 24 – 26 , resulting in gradual decrease in seismic energies with distance. This would lead to a progressive decline in high frequency contents both within and across basins, which cannot explain our observations of the instantaneous depletion of high-frequency energy at the edges of basins (Fig.…”
Section: Seismic Experiments On the 3d Printed Modelmentioning
confidence: 99%
“…High peak delays and high Q c −1 detect intrusions in mountain chains and magmatic systems (De Siena et al, 2016). These parameters are reliable markers of fluid-induced fracturing leading to earthquakes at the regional scale (Borleanu et al, 2017). In fault networks like those ruptured by the AVN, Napolitano et al (2020) found that high-scattering and highabsorption patterns obtained by increasing frequencies map the migration of the historical seismic events from the 16th century until the Pollino seismic sequence.…”
Section: Introductionmentioning
confidence: 99%
“…Takahashi et al (2007) first used peak delay times to map volcanic areas in northeast Japan. High peak delays mark fractured volumes across the Pyrenees , the eastern portion of the Siletz terrane in the Western US (De Siena et al, 2016), and the Vrancea region in Romania (Borleanu et al, 2017). Within fault networks, peak delay increases are visible at all frequencies when waves cross fractured geological volumes, as the carbonates of the Pollino seismic gap, in Southern Italy (Napolitano et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation